Tsenguluso ya u shumiswa ha luambo lwa u nyefula kha lushaka lwa Vhavenda - Muthige, Azwifarwi Gladys (University of Limpopo, 2014)
This research focuses on the use of derogative language in Tshivenḓa discourse. Derogative language is the language used in a society in showing critical or disrespectful attitude. In each and every society, people use derogative language or words in addressing different unacceptable behaviours. Derogative language is used in schools, churches, homes, to mention but a few places. There are factors compelling Vhavenḓa people to use derogative language. In this regard, one may mention social, political, and economic factors. For instance, hardworking people who have amassed wealth through their efforts are sometimes labelled scornful names such as madyavhathu (cannibals) and keepers of maḓuxwane (zombies). Ultimately, the use of derogatory language affects people socially and psychologically.
Thesis (MA. (African Languages)) -- University of Limpopo, 2014
Keywords: Derogative language; Venda language -- Usage; Grammar, Comparative and general